A comparative study of ultrasonography versus anatomical landmark guided techniques for erector spinae plane block in unilateral inguinal hernia surgeries - Ritu Pauranik; Ravindra Semaliya; Aseem Sharma; Manish Banjare; Aradhna Chourasiya (Asian Journal of Medical Sciences)
Background: Hernia surgery can cause immense pain and discomfort postoperatively. Erector spinae plane block (ESPB) is a relatively new method of treating pain associated with various surgical procedures. EPSB can be administered under ultrasonography (USG) guidance or guided by anatomical landmarks.